The Contribution of Individual Morphological Characteristics in the Effectiveness of Human Blastocyst Vitrification - Yurchuk, Taisiya A.; Petrushko, Marina P.; Pinyaev, Vladimir I. (Problems of Cryobiology and Cryomedicine, 2015)
N/A